Civilian penetrating neck trauma at a level I trauma centre: A five‐year retrospective case note review. (14th October 2021) - Zakaria, Benjamin; Muzaffar, Jameel; Borsetto, Daniele; Fussey, Jonathan; Kumar, Raghu; Evans, Kate; Pickering, Christopher; Reid, Conor; Coulson, Christopher; Orr, Linda; Pracy, Paul; Nankivell, Paul; et al.
Abstract: Objectives: To report the experience of civilian penetrating neck trauma (PNT) at a UK level I trauma centre, propose an initial management algorithm and assess the degree of correlation between clinical signs of injury, operative findings and radiological reports. Design: Retrospective case note review. Setting: UK level I trauma centre April 2012–November 2017. Participants: Three hundred ten cases of PNT were drawn from electronic patient records. Data were extracted on hard and soft signs of vascular or aerodigestive tract injury, clinical management, radiological imaging and patient outcomes. Main outcome measures: Patient demographics, mechanism of injury, morbidity and mortality. The correlation between clinical signs, and radiological reports to internal injury on surgical exploration. Results: Two hundred seventy‐one (87.4%) male and 39 (13.6%) female patients with a mean age of 36 years (16–87) were identified. The most common causes of injury were assault 171 (55.2%) and deliberate self‐harm 118 (38%). A knife was the most common instrument 240 (77.4%). Past psychiatric history was noted in 119 (38.4%), and 60 (19.4%) were intoxicated. 50% were definitively managed in theatre with a negative exploration rate of 38%, and 50% were managed in ED. Pre‐operative radiological reports correlated with operative reports in 62% of cases with venous injury the most common positive and negative finding. Multivariate correlation was r  = 0.89, p  = 0.045, between hard signs plus positive radiology findings and internal injury on neck exploration. Conclusions: Management of PNT by clinical and radiological signs is safe and effective, and can be streamlined by a decision‐making algorithm as proposed here.